The Image of History as a Playground - Carmen DOMINTE (Annals of Philosophy, Social and Human Disciplines, 2013)
This study analyzes the problem of history seen as a playground between two different worlds: Eastern and Western Europe. The article draws attention to the relation between the two European regions from the cultural and historical point of view. The two areas may be also seen as two naughty children who consider history a playground. They are the children of history who easily forget that any game implies a certain number of rules and try to disobey them. But any game also implies dialogue between the parts involved. The dialogue between them represents an exchange of words, concepts, attitudes, languages. At the end of the game this particular part of Europe will have its own history made of all the other national histories, its own culture made of all the other national cultures. The Central Europe is the area that was based on multiculturalism that came from the trans-cultural vision of the world.